2006
DOI: 10.1109/tac.2006.876802
|View full text |Cite
|
Sign up to set email alerts
|

Stability of TCP/RED Systems in AQM Routers

Abstract: By applying the time-delay control theory to a TCP/RED dynamic model, this note establishes some explicit conditions under which the TCP/RED system is stable in terms of the average queue length. Then, the stability region is discussed. Finally, the results are illustrated by using 2 simulations, which demonstrates that it is able to choose an appropriate control parameter max of RED based on the stability conditions derived in this note, to achieve satisfactory network performance. It is found, by comparison,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(37 citation statements)
references
References 18 publications
0
36
0
1
Order By: Relevance
“…TCP/RED system becomes unstable when the round-trip delay and link capacity increase, and the number of TCP sessions decreases (Tan et al, 2006). A number of studies how to improve the basic algorithm have appeared; their comparison may be found, e.g., in the work of Hassan and Jain (2004).…”
Section: A Domański Et Almentioning
confidence: 99%
“…TCP/RED system becomes unstable when the round-trip delay and link capacity increase, and the number of TCP sessions decreases (Tan et al, 2006). A number of studies how to improve the basic algorithm have appeared; their comparison may be found, e.g., in the work of Hassan and Jain (2004).…”
Section: A Domański Et Almentioning
confidence: 99%
“…The following linearized fluid model [1], [2] describes the dynamics of the TCP congestion window size and the queue length at the bottleneck router:…”
Section: System Model For Tcp/aqm Wireless Networkmentioning
confidence: 99%
“…Given the ever-increasing demand for Internet access anywhere, anytime, congestion control for wireless networks is critically important. Although the stability of the Internet using TCP congestion control and AQM schemes has been extensively investigated [1], [2], [3], [4], effective congestion control for wireless networks is an open issue.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies in Alpcan and Basar (2005), Guo et al (2007), Liu et al (2005), Low et al (2003), Massoulie (2002), Paganini (2002), Paganini et al (2003), Ranjan et al (2006), Tan et al (2006), Tian (2005a, b), Tian and Yang (2004), Wang et al (2002), Zhang et al (2007) and Ying et al (2006) have successfully dealt with heterogeneous delays, and have obtained several sufficient conditions for the local and global stability of some congestion control algorithms such as the discrete and continuous first-order primal algorithms, the dual algorithms and the primal-dual algorithms. The methods used to investigate the stability issue include the game-theoretic approach, Razumikhin's theorem, and the general Nyquist criterion in frequency domain.…”
Section: Introductionmentioning
confidence: 98%